An energy balancing strategy for modular multilevel converter based grid‐connected photovoltaic systems. Issue 12 (20th April 2021) - Elsanabary, Ahmed; Mekhilef, Saad; Seyedmahmoudian, Mehdi; Stojcevski, Alex
Abstract: Modular multilevel converters (MMC)s are promising candidates for large‐scale grid‐connected photovoltaic (PV) systems. Due to their modular structure, MMCs provide a direct connection of the PV arrays to the converter submodules. They also offer scalability, independent maximum power point tracking, and enhanced power quality with internal power flow capabilities. However, the intermittent nature of PV arrays introduces a power unbalance inside the converter, which affects its operation. This paper addresses the issue and proposes an energy balancing strategy for the grid‐connected MMC‐based PV system. It uses the internally generated leg currents to control the power flow inside the converter and inject a three‐phase balanced current to the grid with low total harmonic distortion. Compared to the existing strategies, the proposed strategy can overcome any condition of the power unbalance with minimal submodule voltage fluctuations. A 162‐kW, 9‐kV PV grid‐connected system is modelled and simulated in MATLAB Simulink environment. The corresponding results are presented to demonstrate the effectiveness of the proposed control strategy for grid‐connected PV systems.